Effects of nordic walking exercise on gait, motor/non-motor symptoms, and serum brain-derived neurotrophic factor in individuals with Parkinson's disease - Harro, Cathy C.; Shoemaker, Michael J; Coatney, Cassandra M.; Lentine, Valerie E.; Lieffers, Lillian R.; Quigley, Jessica J.; Rollins, Shannon G.; Stewart, Jonathan D.; Hall, Julie; Khoo, Sok Kean (Frontiers in Rehabilitation Sciences, 2022)
Objective. The primary purpose of this study was to investigate the immediate and long-term effects of Nordic Walking (NW) exercise on walking function, motor/non-motor Parkinson’s Disease (PD) symptoms, and serum brain-derived neurotrophic factor (BDNF) in persons with idiopathic PD. Methods: Twelve community-dwelling participants with mild to moderate idiopathic PD and varied degrees of gait dysfunction were recruited for this prospective, repeated measures design that examined clinical measures and BDNF levels at baseline (T0), post-intervention (T1) and 3-month follow-up (T2). Participants engaged in 6 weeks of supervised NW exercise training with individualized instruction, followed by 14 weeks of independent NW exercise with remote coaching. Outcome measurements included daily step counts, 6-Minute Walk Test (6-MinWT), 10-Meter Walk Test (10MWT), spatiotemporal parameters, Timed Up and Go Test (TUG), dual-task TUG, Revised-Movement Disorder Society-Unified Parkinson’s Disease Rating Scale (MDS-UPDRS), Revised-Freezing of Gait Questionnaire, MDS-Nonmotor Symptom scale (NMS), Parkinson’s Fatigue Scale, and serum BDNF levels. The Friedman test with post hoc Wilcoxon sign-ranked pairwise comparisons were used to compare baseline to T1, baseline to T2, and T1 to T2 timepoints with a Benjamini-Hockberg correction applied. Results. Statistically significant improvements found post-training and retained at 3-month follow-up included 6-MinWT, daily step count, 10mWT, MDS-UPDRS, and TUG with effect sizes of 0.57 to 1.03. Serum BDNF at T2 was significantly greater than T0 and T1. Although no statistically significant improvements were observed in the MDS-NMS, 9 of 12 participants had improved non-motor symptoms. There was good adherence, sustained independent exercise engagement, and no adverse events over the 5-month study duration. Conclusions. This study demonstrated that NW exercise was a safe, feasible, and sustainable mode of aerobic exercise for this sample of participants with varied Parkinson’s disease duration and severity. Following an individualized and progressive NW training intervention, significant improvements in walking function, daily activity level, and motor function were observed. Following the supervised NW training phase, independent three-month engagement in NW exercise was sustained with long-term retention of these clinical improvements and an increase in serum BDNF levels over this five-month NW exercise trial.